Gradient pores enhance charge storage density of carbonaceous cathodes for zn-ion capacitor - Li, Xinyuan (2024)
Engineering carbonaceous cathode materials with adequately accessible active sites is crucial for unleashing their charge storage potential. Herein, activated meso-microporous shell carbon (MMSC-A) nanofibers are constructed to enhance the zinc ion storage density by forming a gradient-pore structure. A dominating pore size of 0.86 nm is tailored to cater for the solvated [Zn(H2 O)6 ]2+ . Moreover, these gradient porous nanofibers feature rapid ion/electron dual conduction pathways and offer abundant active surfaces with high affinity to electrolyte. When employed in Zn-ion capacitors (ZICs), the electrode delivers significantly enhanced capacity (257 mAh g-1 ), energy density (200 Wh kg-1 at 78 W kg-1 ), and cyclic stability (95% retention after 10 000 cycles) compared to nonactivated carbon nanofibers electrode. A series of in situ characterization techniques unveil that the improved Zn2+ storage capability stems from size compatibility between the pores and [Zn(H2 O)6 ]2+ , the co-adsorption of Zn2+ , H+ , and SO4 2- , as well as reversible surface chemical interaction. This work presents an effective method to engineering meso-microporous carbon materials toward high energy-density storage, and also offers insights into the Zn2+ storage mechanism in such gradient-pore structures.